Dancing Golden Stools: Indigenous Religion as a strategy for identity construction in Ghana - Müller, Louise Françoise (Fieldwork in religion, 2010)
In this article the author concentrates on the use of Indigenous Religion among the Akuapem in Ghana for the construction of their group identity. She discusses the way in which the Akuapem make use of the celebration of an annual indigenous religious festival (Odwira) to strengthen their group identity by self-identification, differentiation and the perception of other cultural groups. Her specific focus is on the common Asante-Akuapem history, the foundation of the Akan Golden Stools, akom dancing and the Odwira festival procession and Durbars. She concludes that Indigenous Religion should not be left out in the study of the construction of group identities in the social sciences.